Wastewater Surveillance of SARS-CoV-2 as Monitoring Tool for COVID-19: A Literature Review - Satyafebrianti, Kendra Callista; Tedjaprasadja, Leonardo; Durry, Fara Disa; Seliana, Irma (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: The COVID-19 pandemic, caused by SARS-CoV-2, has significantly impacted global health, requiring effective surveillance methods. Wastewater surveillance has emerged as a cost-effective and non-invasive tool to detect viral RNA from both symptomatic and asymptomatic individuals, allowing early detection of outbreaks. Objective: This study analyzes the effectiveness of wastewater surveillance in detecting SARS-CoV-2 RNA in untreated wastewater, comparing it with clinical surveillance and evaluating its role in public health monitoring. Method: A literature review was conducted using PubMed, Google Scholar, and Scopus, focusing on studies published between 2015–2025. Articles were selected based on relevance, availability, and originality, applying the PICO strategy to refine the search. From ten initially identified studies, two were selected for in-depth analysis. Result: The findings demonstrate that wastewater surveillance effectively tracks SARS-CoV-2 trends in communities. A study in Brazil showed a strong correlation between viral loads in wastewater and clinical case trends, proving its potential as an early warning system. Meanwhile, research in Australia confirmed the presence of SARS-CoV-2 in wastewater and estimated infection prevalence using Monte Carlo simulation, aligning with reported clinical cases. These studies highlight wastewater surveillance as a reliable tool for population-wide monitoring. Conclusion: Wastewater surveillance is a proven method for detecting SARS-CoV-2, complementing clinical surveillance by enabling early detection, wider coverage, and cost efficiency. Challenges such as RNA degradation and detection standardization require further research, but integrating RT-qPCR and genomic sequencing enhances its accuracy for future epidemiological monitoring.